The Impact of Virtual Surgical Planning on Orthognathic Surgery: Contributions From Two Specialties. Issue 5 (8th July 2022) - Chen, Jonlin; Abousy, Mya; Girard, Alisa; Duclos, Olga; Patel, Viren; Jenny, Hillary; Redett, Richard; Yang, Robin
Abstract : Background: Virtual surgical planning (VSP) has gained popularity for preoperative orthognathic surgery planning and is increasingly being employed by surgeons trained in plastic and reconstructive surgery (PRS) or oral and maxillofacial surgery (OMS). This review assesses the introduction of VSP as a new technology and its impact on orthognathic surgery research and practices based upon surgeon training. Methods: Two PubMed literature reviews were conducted. The first classified publications on VSP for orthognathic surgery by training (OMS- or PRS-trained surgeons) and compared focuses, timing, and journals of publications from each group of surgeons. The second evaluated how orthognathic surgery publication volumes changed with VSP introduction. English articles published from inception until January 2020 (first review) and November 2020 (second review) were included. Results: The first literature review retrieved 419 unique publications, with 188 studies selected for inclusion: 162 were published by OMS-trained principal investigators (OMS-authored) and 26 by PRS-trained principal investigators (PRS-authored). Plastic and reconstructive surgery-authored publications regarding VSP use in orthognathic surgery increased after the first publication in 2000, but at a significantly slower rate (0.2 new publications/year) than OMS-authored publications ( P < 0.01). Aesthetics was discussed in significantly more PRS-authored publications (76.9% compared to 28.4% of OMS-authored publications). The second review revealed that over 80.6% of orthognathic surgery literature was published after 2008, the year VSP was first integrated into orthognathic surgery workflow. Conclusions: Following the introduction of VSP, orthognathic surgery research output has differed between PRS and OMS based on publication speed, volume, and research focuses. Further research is necessary to evaluate how VSP has impacted PRS and OMS clinical practice.